Tariff Rates of the World: Are Customs Duties Really Growing Unimportant? - Carsten Weerth (Global Trade and Customs Journal, 2009)
Some scientists and authorities are arguing that tariffs are growing more and more unimportant since eight GATT/WTO-Tariff-Rounds have resulted in tremendous reductions of the original tariff rates in the late 1940ies. The Non-Tariff-Measures however are gaining more importance. A WCO-background-paper has been published in September 2008 which shows the amount of revenue of a state that is generated by customs duties. The results are amazing. Tariffs are not important any more for developed states however revenue from customs duties is of very much importance to the (least) developing countries. The WCO-background-paper is based on data of 142 countries, territories and economic unions (all referred to as 'countries').
Keywords: K33; K34; H20; F53; 330; Customs Law; World Trade Organization; GATT; World Customs Organization